Lesson plan and the english language learning with the students of 8th, 9th and 10th years of basic education at Pío Jaramillo Alvarado high school of Loja city, academic year 2012-2013 - Jumbo Cardenaz, Mirian Mercedes (2015)
The research work “LESSON PLAN AND THE ENGLISH LANGUAGE LEARNING WITH THE STUDENTS OF 8TH, 9TH AND 10TH YEARS OF BASIC EDUCATION AT “PÍO JARAMILLO ALVARADO” HIGH SCHOOL OF LOJA CITY, ACADEMIC YEAR 2012-2013” has as main objective to determine the influence of the Lesson Plan on the English Language Learning with the students of 8TH, 9TH AND 10TH years of Basic Education at “PIO JARAMILLO ALVARADO” High School of Loja City Academic Year 2012-2013. The main used method was the scientific which helped to find the truth about the researched object. Also it was necessary to use the descriptive, analytic, synthetic and explicative methods to develop this work. The survey was the technique applied to three teachers and 79 students. The results conclude that teachers are not taking into account the aspects in a Lesson plan and activities that wake up the students´ interest in the English Language Process.